SCREENING OF PUTATIVE THERAPEUTIC CANDIDATES IN SUPERBUG (STAPHYLOCOCCUS AUREUS): A SYSTEMATIC IN SILICO APPROACH - Zaveri, Kunal; Patnala, Kiranmayi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Staphylococcus aureus, a superbug and antibiotic resistant pathogen, is one of the most infection causing organism, ranging from skin allergies to severe lethal conditions. The prolonged use of different antibiotics and lack of optimal treatment over the antibiotic resistant species, led to the identification of new, better and promising therapeutic candidates. Methods: A systematic in silico filtration process was employed, which includes subtractive channels and reverse vaccinology techniques. Results: Here, we report 12 possible drug targets and two vaccine candidates based on essentiality, non-human homolog, virulent and localization, commonly in all the strains. Further characterization studies such as pathway analysis, chokepoint and structure prediction revealed, two proteins as the best drug targets one being novel and the other druggable. Only one protein has shown the characteristic feature of vaccine candidate, having antigenic property and an IgG binding domain. Conclusion: Two best drug targets were commonly identified in all the strains of S. aureus namely UDP-N-acetylmuramoyl-L-alanyl-D-glutamate--L-lysine ligase (MurE) and cell division protein FtsA, whereas the best common vaccine candidate includes Peptidoglycan binding protein. The therapeutic candidates reported in the present study might facilitate screening of new and better antimicrobial compounds, for an optimal treatment of S. aureus infections. Keywords: Staphylococcus aureus, Drug target, Vaccine candidates, Subtractive proteomics, Reverse vaccinology.